PEMBAURAN BUDAYA DAN HARMONI ETNIS: INTERAKSI ANTARA ETNIS TIONGHOA DAN MASYARAKAT LOKAL DI KOTA PEMATANG SIANTAR - Soffia Aqila; Alfi Syahrin Hasibuan; Vanesia Amelia Sebayang; Lila Pelita Hati (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
This research discusses the role and interaction of ethnic Chinese with local communities in Pematang Siantar City, North Sumatra. Ethnic Chinese have been present since the 16th century as Dutch traders and contract workers, growing to become an integral part of the local community. Despite conflicts at some points in time, many positive examples show that cross-cultural collaboration results in benefits for both parties. The research method used is qualitative, with data collection through field observations, interviews, and documentation. The results show that ethnic Chinese have made significant contributions to the city's economy, culture and education, creating a rich cultural diversity. Cultural blending occurs through socialization, cultural acculturation, vocabulary, language, culinary, and cultural celebrations. The local government is active in facilitating culture and the promotion of inter-ethnic social harmony. This research is expected to be a source of information about the contribution of Chinese culture to the social and cultural life of local communities in Pematang Siantar City.